The Effect of Five-Finger Relaxation Technique to The Sleep Quality of Breast Cancer Patients - Rosliana Dewi; Laili Rahayuwati; Titis Kurniawan (JKP (Jurnal Keperawatan Padjajaran), 2018)
Sleeping disorder is a symptom often suffered by breast cancer patients. To overcome it, five-finger relaxation technique is considered helpful. In previous research, this technique can be utilized to lower the level of anxiety and fatigue. This research, therefore, aims at identifying the effect of five-finger relaxation technique to the sleep quality of breast cancer patients.